The Impact of Policy Networks in the Implementation of E Government in Indonesia - Ilhami, Rizky (Paspama Institute, 2023)
The implementation of E-Government in Indonesia has become a major concern in efforts to increase the efficiency and transparency of public services. However, the complexity of implementing this program cannot be separated from the dynamic interactions between various policy networks that influence its direction and impact. This research aims to analyze the impact of policy networks in implementing E-Government in Indonesia. The research method used is a qualitative approach with a focus on policy analysis and case studies of E-Government implementation in several selected provinces. Data was obtained through in-depth interviews with key stakeholders, analysis of policy documents, and direct observation of the implementation process. The research results show that the implementation of E-Government in Indonesia is greatly influenced by the complexity of the policy network which includes legal regulations, inter-institutional coordination, as well as political and cultural factors. Overlapping policies between institutions often hinder program alignment and effectiveness, while a lack of coordination between institutions slows down holistic decision-making processes. However, the development of effective policy networks can facilitate stakeholder identification, improve inter-institutional coordination, improve policy quality, and encourage innovation and adaptation in the development of public services, which can ultimately improve the quality and accessibility of public services as a whole.